Modern foraminifera assemblages in the Amundsen Sea Embayment - Jernas, Patrycja Ewa; Kuhn, Gerhard; Hillenbrand, Claus-Dieter; Forwick, Matthias; Rasmussen, Tine Lander; Mackensen, Andreas; Schröder, Michael; Smith, James; Klages, Johann Philipp; Szczucinski, W (31st geological winter meeting: Vinterkonferansen 2015, 2015)
The West Antarctic Ice Sheet (WAIS) is considered the most unstable part of the Antarctic Ice Sheet. As the WAIS is mostly grounded below sea level, its stability is of great concern. A collapse of large parts of the WAIS would result in a significant global sea-level rise. At present, the WAIS shows dramatic ice loss in its Amundsen Sea sector, especially in Pine Island Bay. Pine Island Glacier (PIG) is characterised by fast flow, major thinning and rapid grounding-line retreat. Its mass los over recent decades is generally attributed to melting caused by the inflow of warm Circumpolar Deep Water (CDW). Future melting of PIG may result in a sea level tipping point, because it could trigger widespread collapse of the WAIS, especially when considering ongoing climate change.
Keywords: Sørishavet; geologi; innlandsis; klimaendringer

Modern foraminifera assemblages in the Amundsen Sea Embayment - Jernas, Patrycja Ewa; Kuhn, Gerhard; Hillenbrand, Claus-Dieter; Rasmussen, Tine Lander; Forwick, Matthias; Mackensen, Andreas; Schröder, Michael; Smith, James; Klages, Johann Philipp (EGU General Assembly 2015, 2015)
The West Antarctic Ice Sheet (WAIS) is considered the most unstable part of the Antarctic Ice Sheet. As the WAIS is mostly grounded below sea level, its stability is of great concern. A collapse of large parts of the WAIS would result in a significant global sea-level rise. At present, the WAIS shows dramatic ice loss in its Amundsen Sea sector, especially in Pine Island Bay. Pine Island Glacier (PIG) is characterised by fast flow, major thinning and rapid grounding-line retreat. Its mass los over recent decades is generally attributed to melting caused by the inflow of warm Circumpolar Deep Water (CDW). Future melting of PIG may result in a sea level tipping point, because it could trigger widespread collapse of the WAIS, especially when considering ongoing climate change.
Keywords: Sørishavet; geologi; innlandsis; klimaendringer